2019
DOI: 10.1002/pmrj.12147
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Osseointegration: A National Survey of Veterans with Upper Limb Amputation

Abstract: Introduction: Osseointegrated (OI) prostheses have a unique benefit-risk profile among prosthetic alternatives and have been marketed in the United States under a Humanitarian Device Exemption since 2015. Information about upper limb prosthesis user perspectives on benefits and risks, prosthesis-user subpopulations for whom OI is most acceptable, and outcomes that matter most to patients could help inform clinical and regulatory decision-making. Recent 21st Century Cures legislation expanded the role of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Ultimately, a better fitting of the osseointegrated prosthesis resulted in better patient satisfaction and integration of the prosthetic device into the daily life activities, as reported by all eight studies included in this review. Moreover, a recent patient perspective study by Resnik et al 27 reported that more than 20% of patients with unilateral amputations are willing to consider OI surgery to gain better prosthetic control. The results of the included studies do not only emphasize a more durable and reliable fixation of the prosthetic device compared with the conventional socket fitting but also report on the improvement in terms of comfort from the patients’ perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, a better fitting of the osseointegrated prosthesis resulted in better patient satisfaction and integration of the prosthetic device into the daily life activities, as reported by all eight studies included in this review. Moreover, a recent patient perspective study by Resnik et al 27 reported that more than 20% of patients with unilateral amputations are willing to consider OI surgery to gain better prosthetic control. The results of the included studies do not only emphasize a more durable and reliable fixation of the prosthetic device compared with the conventional socket fitting but also report on the improvement in terms of comfort from the patients’ perspective.…”
Section: Discussionmentioning
confidence: 99%
“…40 Finally, in a large study in Veterans with a diagnosis of major upper limb amputation who were surveyed by telephone indicated that about 41% of amputees would consider surgery to restore a sense of touch, while 49% indicated they would consider surgery to gain more movement control. 41 Our study is informed by these studies, but unique in using choice based conjoint analysis to ask those with ULL to directly weigh the risks and benefits of osseointegration and myoelectric control choices. We found that patients preferred complete independence in cooking dinner above all other positive attributes which likely reflects their desire for independence in their daily life tasks.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Finally, in a large study in Veterans with a diagnosis of major upper limb amputation who were surveyed by telephone indicated that about 41% of amputees would consider surgery to restore a sense of touch, while 49% indicated they would consider surgery to gain more movement control. 41 …”
Section: Introductionmentioning
confidence: 99%
“…Although preliminary long-term assessments have indicated improved quality of life for individuals who have undergone osseointegration 45 , large-scale cohort studies with long follow-up periods are needed to assess the safety and performance outcomes of the procedure. A survey of the veteran population in the on United States reported that only 28% of unilateral limb amputees and 13% of bilateral upper-limb amputees would consider osseointegration rather than traditional fixation of the device via a conventional socket or refraining from using any prosthesis 46 .…”
Section: Biomechanical Interfacesmentioning
confidence: 99%